2007
DOI: 10.1007/s10389-007-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the causes of malaria and of its complications, treatment and prevention among midwives and pregnant women of Eastern Sudan

Abstract: Background Malaria infection during pregnancy is a big burden in Sudan and has many adverse effects on both mother and fetus. There are no data concerning the local socio-cultural knowledge of malaria, its complications and prevention during pregnancy. Aim This study was conducted to assess the perceptions of the causes of malaria, its complications, treatment and prevention among midwives and pregnant women of Eastern Sudan so as to provide policy makers and malaria programme managers with information needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
3
16
0
Order By: Relevance
“…The association of febrile illness with malaria has been known in Bangladesh for a long time [ 23 ]. This is also reiterated in this study, where the majority of the respondents mentioned fever (with shivering, at intervals) as the most common symptom of malaria and is consistent with observations from other countries [ 16 , 18 , 20 , 21 , 24 - 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The association of febrile illness with malaria has been known in Bangladesh for a long time [ 23 ]. This is also reiterated in this study, where the majority of the respondents mentioned fever (with shivering, at intervals) as the most common symptom of malaria and is consistent with observations from other countries [ 16 , 18 , 20 , 21 , 24 - 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The follow-up survey shows improvement in some of the knowledge indicators such as the most common symptom suggestive of malaria, comparable to other countries such as eastern Sudan [16], Nepal [17], Turkey [18] and Iran [19]. Also, the dramatic improvement in knowledge regarding the importance of insecticidal bed nets for the prevention of malaria following awareness campaigns has also been observed in other studies [17], [20].…”
Section: Discussionsupporting
confidence: 75%
“…It could also be due to the proximity of the chemist shops which does not require any protocols before services can be rendered. Adams et al [31] reported that managing malaria fever has been shown to be related to cost, availability and cultural beliefs about the causes of disease. The reported high patronage of chemist shops by the Kitaku clan when compared to other clans may also be linked to the convenience of service and accessibility of drugs from the patent medicine stores.…”
Section: Management Of Fevermentioning
confidence: 99%